Methodological Aspects of Training English Speaking Competences for Specialists in Economics, International Relations and Business Administration: a Communicative Approach // Pedagogy Тheory: Innovation in Еducation, Тeaching Рractice and Мethods - Poliakova Yuliia; Stepanov Andriy (Boston Primedia eLaunch, 2020)
The relevance of foreign language proficiency and its teaching in the system of higher education is due to the development of international cooperation between countries in economic, cultural, educational and other fields. In the globalised society, we observe every year the growing number of businesses cooperating with foreign partners. Working in modern multinational companies requires possession of foreign language skills. The status of English in the world as a language of international communication distinguishes it from others and makes it a promising communicative tool for study and practical application in modern society. We believe that the above mentioned factors determine the methodological aspect of linguistic preparation of future specialists. Therefore, one of the most important aspects of learning any foreign language is the formation of oral communicative skills, which occupies a leading place in the training program in accordance with the ministerial and university requirements. the methodical approach to developing communicative competences is carried out with a system that includes: the sequence of processing material, reliance on patterns and models of dramatizing dialogues in accordance with the use of real speech situations, the development of creativity of the students. The generalized experience of formation and development of oral communicative competence, in particular through dialogues, is directly related to teaching English as a Foreign Language for students majoring in Business and Administration, International Relations, Economics, but can be used in teaching English to students of other economic related specialties. The proposed inventory of methods and techniques can be changed and supplemented and applied according to any individual approach of the teacher.
Keywords: language acquisition; language competences; foreign language proficiency; methodical approaches; communicative skills